Quality Management of Online Learning Environments : Final Report of the Project, Building Distributed Leadership in Designing and Implementing a Quality Management Framework for Online Learning Environments. - Holt, Dale; Palmer, Stuart; Munro, Judy; Solomnides, Ian; Gosper, Maree; Allan, Garry; Hollenbeck, Robert; Hicks, Margaret; Sankey, Michael (Office for Learning and Teaching, 2014)
Final report from a project that designed and implemented a framework using a distributed leadership approach for the quality management of online learning environments in Australian higher education. The distributed leadership approach enabled the development of the framework and, in turn, contributed to its implementation. The framework was the vehicle for building leadership capacity. The project drew upon the combined expertise and strengths of five universities using different learning management systems and approaches to social networking and which were at various stages of deploying their next-generation online learning environments. The universities involved represented different groupings of institutions in the sector and each was reliant on disparate leadership groups to successfully implement and sustain their environments.